Efeito nefroprotetor do óleo essencial de Lippia alba (MILL.) N.E. Brown (Erva-cidreira) quimiotipo II em modelos de isquemia e reperfusão - Cavalcanti, Mariana Maciel (2018)
Ischemia and Reperfusion (I/R) is one of the main triggering factors for acute renal injury (AKI). This process leads to the formation of reactive oxygen species (ROS) that cause cellular oxidative stress. Natural antioxidant substances are widely researched to treat this type of I/R injury, including essential oils such as Lippia alba (lemon balm), which produces essential oil rich in antioxidants such as citral and limonene. Thus, this study aims to analyze the possible nephroprotective effect of Lippia alba essential oil on AKI in Ischemia and Reperfusion (I/R) models. For this, male Wistar rats (~ 200-250g) were submitted to right nephrectomy and clamping of the left renal artery, and renal injury was established. Next, the surgery was performed on animals, which received the essential oil of Lippia alba (200mg/kg- intraperitoneal). Blood, urine and renal tissue samples were collected for biochemical evaluations (creatinine, urea, uric acid, creatinine clearance, proteinuria and microalbuminuria) and antioxidant analyzes (MDA and GSH). The study was approved by the Animal Research Ethics Committee of the Federal University of Ceará (nº 110/2017). In addition, an in vitro I/R model was performed using LLC-MK2 and HK-2 renal tubule cell lines for cell viability analysis by MTT reduction, as well as evaluation of cell ultrastructural changes by Electron Microscopy Scanning (SEM). Data were expressed as mean ± standard error of the mean and as significance criterion was accepted p <0.05. Lippia alba essential oil presented the renal protection capacity in the in vivo experiment, reducing creatinine, urea, uric acid and increasing creatinine clearance in the treated groups, as well as reducing oxidative stress. In the in vitro assay, the oil was able to reverse the injury by I/R. With this, it was observed that the essential oil of Lippia alba presented as a promising substance in the prevention or reduction of acute renal injury, since, through possible antioxidant mechanisms led to nephroprotection in the I/R models.